The Emerging Role of Altered d-Aspartate Metabolism in Schizophrenia: New Insights From Preclinical Models and Human Studies - Errico, Francesco; Nuzzo, Tommaso; Carella, Massimo; Bertolino, Alessandro; Usiello, Alessandro (Frontiers in Psychiatry, 2018)
Besides D-serine, another D-amino acid with endogenous occurrence in the mammalian brain, D-aspartate, has been recently shown to influence NMDA receptor (NMDAR)-mediated transmission. D-aspartate is present in the brain at extracellular level in nanomolar concentrations, binds to the agonist site of NMDARs and activates this subclass of glutamate receptors. Along with its direct effect on NMDARs, D-aspartate can also evoke considerable L-glutamate release in specific brain areas through the presynaptic activation of NMDA, AMPA/kainate and mGlu5 receptors. D-aspartate is enriched in the embryonic brain of rodents and humans and its concentration strongly decreases after birth, due to the post-natal expression of the catabolising enzyme D-aspartate oxidase (DDO). Based on the hypothesis of NMDAR hypofunction in schizophrenia pathogenesis, recent preclinical and clinical studies suggested a relationship between perturbation of D-aspartate metabolism and this psychiatric disorder. Consistently, neurophysiological and behavioural characterization of Ddo knockout (Ddo-/-) and D-aspartate-treated mice highlighted that abnormally higher endogenous D-aspartate levels significantly increase NMDAR-mediated synaptic plasticity, neuronal spine density and memory. Remarkably, increased D-aspartate levels influence schizophrenia-like phenotypes in rodents, as indicated by improved fronto-hippocampal connectivity, attenuated prepulse inhibition deficits and reduced activation of neuronal circuitry induced by phencyclidine exposure. In healthy humans, a genetic polymorphism associated with reduced prefrontal DDO gene expression predicts changes in prefrontal phenotypes including greater gray matter volume and enhanced functional activity during working memory. Moreover, neurochemical detections in post-mortem brain of schizophrenia-affected patients have shown significantly reduced D-aspartate content in prefrontal regions, associated with increased DDO mRNA expression or DDO enzymatic activity. Overall, these findings suggest a possible involvement of deregulated embryonic D-aspartate metabolism in schizophrenia pathophysiology and, in turn, highlight the potential use of free D-aspartate supplementation as a new add-on therapy for treating the cognitive symptoms of this mental illness.